Cultural Representation in English Textbook for Junior Highschool - Santosa, Imam (Universitas Esa Unggul, 2015)
This study aims to find out kind of culture in language that existed in English for Junior high school textbook and to identify the categories of culture in English for Junior high school textbook. The study employs a content analysis as a research methodology to explore the culture components in Electronic English Textbook for Junior high school in Indonesia. The study analyzes two main points-cultural features in the textbook and cultural categories. The cultural feature comprises four different features; aesthetic, sociological, semantic and sociolinguistic. The cultural categories consist of target culture, source culture, and other culture. The result of this study shows that appearance of sociological sense dominates all forms of the textbook. The second one dominated is aesthetics sense. Then local culture has a major appearance (48,8%). It can be concluded that the books have intention to make the cultural features that bring meaning or show the character of Indonesia. It indicates that the government had successfully delivered and rendered basic philosophy of curriculum 2013.Keywords: English Textbook, Culture, Cultural Representation Penelitian ini bertujuan untuk mengetahui jenis budaya dalam bahasa yang ada dalam bahasa Inggris untuk SMP buku sekolah tinggi dan untuk mengidentifikasi kategori budaya dalam bahasa Inggris untuk SMP buku sekolah tinggi. Studi ini menggunakan analisis isi sebagai metodologi penelitian untuk mengeksplorasi komponen budaya dalam elektronik English Textbook untuk SMP di Indonesia. Studi ini menganalisis fitur dua utama poin-budaya di buku teks dan kategori budaya. Fitur budaya terdiri dari empat fitur yang berbeda; estetika, sosiologis, semantik dan sosiolinguistik. Kategori budaya terdiri dari budaya sasaran, budaya sumber, dan budaya lainnya. Hasil penelitian ini menunjukkan bahwa munculnya rasa sosiologis mendominasi segala bentuk buku teks. Yang kedua didominasi adalah estetika akal. Kemudian budaya lokal memiliki penampilan utama (48,8%). Dapat disimpulkan bahwa buku memiliki niat untuk membuat fitur budaya yang membawa makna atau menunjukkan karakter Indonesia. Hal ini menunjukkan bahwa pemerintah telah berhasil dikirim dan diberikan filosofi dasar kurikulum 2013.Kata Kunci: Buku Bahasa Inggris, Budaya, Representasi Budaya